2018
DOI: 10.1002/2018gl077004
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Algorithm of Neural Network for the Parameterization of Typhoon‐Ocean Feedback in Typhoon Forecast Models

Abstract: Two algorithms based on machine learning neural networks are proposed—the shallow learning (S‐L) and deep learning (D‐L) algorithms—that can potentially be used in atmosphere‐only typhoon forecast models to provide flow‐dependent typhoon‐induced sea surface temperature cooling (SSTC) for improving typhoon predictions. The major challenge of existing SSTC algorithms in forecast models is how to accurately predict SSTC induced by an upcoming typhoon, which requires information not only from historical data but m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 32 publications
0
77
0
Order By: Relevance
“…It is now predicted that deep learning is going to transform many industries as well as society through developments in health care, education, and business. Deep learning has been applied in fields like bioinformatics [27], medicine and health care [28], space information and weather forecasting [29], education [30], traffic and transportation [31,32], agriculture [33], robotics [34], and gaming [35].…”
Section: Applications Of Deep Learningmentioning
confidence: 99%
“…It is now predicted that deep learning is going to transform many industries as well as society through developments in health care, education, and business. Deep learning has been applied in fields like bioinformatics [27], medicine and health care [28], space information and weather forecasting [29], education [30], traffic and transportation [31,32], agriculture [33], robotics [34], and gaming [35].…”
Section: Applications Of Deep Learningmentioning
confidence: 99%
“…Buscombe and Carini, ; Buscombe et al ., ; Buscombe and Ritchie, ; Linville et al . ; Luo et al ., ; Jiang et al ., ; Reichstein et al ., ). The basic premise of applications such as these, compared to those of other machine learning subcategories, is that it circumvents the need (and the effort required) to make decisions about what extracted image features are important to a specific task, which tends to make the models both more subjective and more powerful.…”
Section: Introductionmentioning
confidence: 99%
“…The NN convection parameterization was tested in the NCAR Community Atmospheric Model (CAM) and produced reasonable and promising results for the tropical Pacific region. Jiang et al (2018) developed a deep NN-based algorithm or parameterization to be used in the WRF model to provide flow-dependent typhooninduced sea surface temperature cooling. Results based on four typhoon case studies showed that the algorithm reduced maximum wind intensity error by 60 %-70 % compared with using the WRF model.…”
Section: Introductionmentioning
confidence: 99%